A mediação da informação para usuários com deficiência visual e sua transformação com o avanço da tecnologia: um estudo de caso na seção Braille da Biblioteca Pública Arthur Vianna - LIMA, Danna Patricia Vieira de (2018)
Mediation of information for users with visual impairment and your transformation with the advancement of technology: a case study in Braille section Arthur Vianna public library, had as objective the analysis of how the mediation of information has become with the advancement of technology for users with visual impairment, in order to meet the changes that cause the technologies of information and mediation as the librarian has handled this transition. The methodology used was the case study in the Public Library's Braille section Arthur Vianna, the documentary research on the activity reports annual plans and activities of the section and semi-structured interview with semi-open questions with professionals working in the industry for over 5 years. The analysis was based on 6 annual reports and annual plans and 4 the applied interview 4 information professionals being 2 librarians and teachers 2 exercising the position of administrative assistant. After the use of methodological tools, infers that the technological advancement facilitated the integration of visually impaired users in the informational field, the emergence of new technologies allowed changes in information mediation, which restricted to use just a prop. The professional librarian has the role of social worker and mediator for inclusion and autonomy of people with visual impairment. Although the existence of technologies in the section there is a need for more advanced brackets for better stability.